Ultrafast and long-time excited state kinetics of an NIR-emissive vanadium(iii) complex I: synthesis, spectroscopy and static quantum chemistry. Issue 32 (22nd July 2021) - Dorn, Matthias; Kalmbach, Jens; Boden, Pit; Kruse, Ayla; Dab, Chahinez; Reber, Christian; Niedner-Schatteburg, Gereon; Lochbrunner, Stefan; Gerhards, Markus; Seitz, Michael; Heinze, Katja
Abstract : Vanadium is an abundant and cheap metal but near-infrared luminescent vanadium complexes are extremely rare with largely unexplored photophysics and photochemistry. We delineate the photodynamics of VCl3 (ddpd) to infer novel design strategies. Abstract : In spite of intense, recent research efforts, luminescent transition metal complexes with Earth-abundant metals are still very rare owing to the small ligand field splitting of 3d transition metal complexes and the resulting non-emissive low-energy metal-centered states. Low-energy excited states decay efficiently non-radiatively, so that near-infrared emissive transition metal complexes with 3d transition metals are even more challenging. We report that the heteroleptic pseudo-octahedral d 2 -vanadium(iii ) complex VCl3 (ddpd) (ddpd = N, N ′-dimethyl- N, N ′-dipyridine-2-yl-pyridine-2, 6-diamine) shows near-infrared singlet → triplet spin–flip phosphorescence maxima at 1102, 1219 and 1256 nm with a lifetime of 0.5 μs at room temperature. Band splitting, ligand deuteration, excitation energy and temperature effects on the excited state dynamics will be discussed on slow and fast timescales using Raman, static and time-resolved photoluminescence, step-scan FTIR and fs-UV pump-vis probe spectroscopy as well as photolysis experiments in combination with static quantum chemical calculations. These results inform future design strategies for molecular materials of Earth-abundant metal ions exhibiting spin–flip luminescence and photoinduced metal–ligand bond homolysis.